Using game engines for wideband channel estimation parameters in Andean cities (2010)
This paper shows the results obtained with a new raytracing method using an open source game engine and high performance graphic cards for the estimation of path loss and parameters of wide-band channel with high accuracy, for both low or high base-station in some specific outdoor urban Andean scenario as is the Cost 2100 Cali reference scenario. We use the algorithms and techniques developed by the game community together with graphics hardware accelerators for parameters estimation in time and frequency for wide-band channels. We use a 3D model dynamically obtained from raster digital elevation model (DEM) with information about constitutive parameters of materials and compare it with measurements, obtaining a good fit.